Customer Loyalty, A Reality Or An Allegory: Exposing Dick And Basu (1994) Loyalty Segmentation Model In Bindura Fast-Food Industry - Kufakunesu, Faustino; Kapesa, Tonderai; Takundwa, Tapiwa (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of the study was to expose the reality about customer loyalty in developing countries using a case of Bindura fast-food industry. Customer loyalty is a very popular subject in the field of marketing. The majority of researches on customer loyalty were carried out in developed economies. To bridge the geographical gap, this study was conducted in a ‘third-world’ economy of Zimbabwe. Descriptive, correlational research designs were adopted backed by both quantitative and qualitative research paradigms. The research used primary data collected from 80 final consumers and 10employees selected through purposive sampling. The study indicated that, the majority of consumers in developing countries are not genuinely loyal to one supplier, but they continuously look for better alternatives basing on situational factors. It is therefore recommended that, new entrepreneurs must not hesitate to venture into new and existing industries assuming that customers belong to existing players.